Alternative revenue streams for centrally funded sport governing bodies - Berry, R.; Manoli, A. I. (International Journal of Sport Policy and Politics, 2018)
In a world of ever-increasing focus on Government spending as a result of recession-induced austerity measures, the current Government of the United Kingdom has clarified its intention to share and ultimately transfer the burden of funding to those sports that currently enjoy Government support. Outside the sports that, due to their wide commercial and broadcast appeal are able to derive significant revenues, it will become necessary for national governing bodies (NGBs) to cast the net wide in search of consistent, reliable methods of generating revenues that satisfy broader stakeholder aims while maintaining focus on their core responsibilities of sport development, encouraging participation and driving performance. In order to unpick this process, interviews were undertaken with senior officials from non-commercialised NGBs to better grasps the current situation and what steps are being taken to secure funding with further exploration of the impact of these new streams. Using Pfeffer and Salancik`s Resource Dependence Theory and Markowitz`s Portfolio Theory, this study examines the revenue streams currently explored by the NGBs, as well as their associated benefits and pitfalls. Through this research, it was found that the applicability of each stream was largely dependent on the unique characteristics of each body. Size and demographics of membership or participants, the degree of formality of participation, local or regional importance of the sport and commercial appeal to potential sponsors and partners, all drove the particular mix of revenue streams achieved by NGBs, making generalisation or the creation of a usable, common template difficult as a result.